1992
DOI: 10.21273/hortsci.27.7.847
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-Humic-Algal Root Biostimulant Increases Yield of Green Bean

Abstract: Over the past decade there has been a notable increase of research on the use of naturally derived or organic materials in agriculture (Poincelot, 1986; Russo and Berlyn, 1990). Some of these are biostimulants, i.e., nonnutritional products that may reduce fertilizer use and increase yield and resistance to water and temperature stresses. Among the materials that stimulate plant growth in relatively small amounts (Aitken et al., 1964; Berlyn and Russo, 1990; Kinnersley et al., 1989; Senn, 1987; Senn and Kingma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 3 publications
2
12
0
1
Order By: Relevance
“…The increase of yield in rocket was particularly observed at the lowest nutrient concentration. These results are in according with the most part of published literature (Russo and Berlyn, 1992;Jana and Paria, 1996). The higher production of rocket plants grown in the floating system with biostimulant may be explained by the increased values of root biomass that probably improved the nutrient use efficiency.…”
Section: Discussionsupporting
confidence: 88%
“…The increase of yield in rocket was particularly observed at the lowest nutrient concentration. These results are in according with the most part of published literature (Russo and Berlyn, 1992;Jana and Paria, 1996). The higher production of rocket plants grown in the floating system with biostimulant may be explained by the increased values of root biomass that probably improved the nutrient use efficiency.…”
Section: Discussionsupporting
confidence: 88%
“…Humic acid effectively improves soil fertility and crop production especially in poor soils and alkalinecalcareous soils (Rajaei, 2010). Our results is supported by the finding of Russo and Berlyn (1992) and Hao and Papadopoulos (2003) who reported that HA sprays increased fruit yield and reproductive growth of tomato and increasing of some elements in plant tissues. Foliar application of HA promoted growth and increased yield by 10.5% in processing tomatoes over untreated controls (Brownell et al, 1987).…”
Section: Absorption In Grain Treatmentssupporting
confidence: 91%
“…Kugrens noted that sometimes potent inhibition occurred when the extracts from M. aeruginosa and A. flos-aquae were mixed together but when taken individually, cotyledon fresh weight actually increased. Promotion of the growth of higher plants by extracts from cyanophytes and algae has been reported by other investigators, for example, Bentley-Mowat and Reid [1968], Gupta and Shukla [1968], Gupta and Gupta [1973], and Russo and Berlyn [1992].…”
Section: Antibiotic Activity Of Algaementioning
confidence: 53%